Free lipid A and full-length lipopolysaccharide coexist in Vibrio parahaemolyticus ATCC33846. (January 2023) - Huang, Danyang; Ji, Fan; Tan, Xin; Qiao, Jun; Li, Hedan; Wang, Zhen; Wang, Xiaoyuan
Abstract: Lipid A plays an important role in the pathogenicity and antimicrobial resistance of Vibrio parahaemolyticus, but little is known about the structure and biosynthesis of lipid A in V. parahaemolyticus . In this study, lipid A species were either directly extracted or obtained by the acid hydrolysis of lipopolysaccharide from V. parahaemolyticus ATCC33846 cells and analyzed by thin-layer chromatography and high-performance liquid chromatography-tandem mass spectrometry. Several lipid A species in V. parahaemolyticus cells were characterized, and two of these species were not connected to polysaccharides. One free lipid A species has the similar structure as the hexa-acylated lipid A in Escherichia coli, and the other is a hepta-acylated lipid A with an additional secondary C16:0 acyl chain. Three lipid A species were isolated by the acid hydrolysis of lipopolysaccharide: the 1 st one has the similar structure as the hexa-acylated lipid A in E. coli, the 2 nd one is a hepta-acylated lipid A with an additional secondary C16:0 acyl chain and a secondary 2-OH C12:0 acyl chain, and the 3 rd one is equal to the 2 nd species with a phosphoethanolamine modification. These results are important for understanding the biosynthesis of lipid A in V. parahaemolyticus. Highlights: Free lipid A species were found in Vibrio parahaemolyticus for the first time. Free lipid A and lipid A covalently linked to LPS coexist in V. parahaemolyticus. The structure of free lipid A could be different from that of lipid A linked to LPS.